Gender Equality in The Education System at Al-Azhar Mandiri Palu Foundation - Fikri Hermawan Yudianto; Nuraedah; Haliadi; Lukman Nadjamuddin (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research aims to find out about the application of gender equality in the education system for schools under the auspices of the Al-Azhar Mandiri Palu Foundation. This study aims to find out about the application of gender equality in the education system for schools under the auspices of the Al-Azhar Mandiri Palu Foundation. The object of this research is the education system that applies in schools under the auspices of the Al-Azhar Mandiri Palu Foundation and also looks at the infrastructure contained in these schools, whether in accordance with its function and role in realising gender equality. This type of research is descriptive research using observation methods complemented by interview methods to several sources related to how gender equality is applied in schools under the auspices of the Al-Azhar Mandiri Palu Foundation. The results of this study indicate that in the education system implemented at the Al-Azhar Mandiri Palu Foundation, gender equality has been implemented, not only for students but also for teachers and educators at all school levels, starting from elementary, junior high and high school. This is evidenced by interviews conducted by researchers and supported by facts in the field in the form of infrastructure and the application of the gender equality system. Although the application of gender equality is not running one hundred percent, the functions and roles of gender are understood by students, teachers and educators at the Al-Azhar Mandiri Palu Foundation.